1999
DOI: 10.1016/s0735-1097(99)00251-x
|View full text |Cite
|
Sign up to set email alerts
|

Desensitization of the pulmonary adenylyl cyclase system

Abstract: In heart failure, the down-regulation of pulmonary beta-receptors and concomitant decrease in adenylyl cyclase activity result in a significant attenuation of cAMP-mediated airway relaxation. These mechanisms may play a pivotal role in the pathogenesis of"cardiac asthma."

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 19 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…Indeed, in clinical practice it is often observed that patients with severe HF lack pulmonary rales on examination or alveolar edema on chest x-ray. Theoretically, the increase in pulmonary capillary hydrostatic pressure and wall tension due to the rise in LV filling pressure consistent with a failing LV (1) combined with down-regulation of the β receptors that are central to lung fluid removal mechanisms (24) secondary to a chronic increase in adrenergic drive should serve to make HF patients more susceptible to lung fluid accumulation relative to their healthy counterparts. However, it has also been shown that pulmonary microvascular permeability is decreased in severe HF patients, which would be expected to protect such patients from pulmonary edema (24).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, in clinical practice it is often observed that patients with severe HF lack pulmonary rales on examination or alveolar edema on chest x-ray. Theoretically, the increase in pulmonary capillary hydrostatic pressure and wall tension due to the rise in LV filling pressure consistent with a failing LV (1) combined with down-regulation of the β receptors that are central to lung fluid removal mechanisms (24) secondary to a chronic increase in adrenergic drive should serve to make HF patients more susceptible to lung fluid accumulation relative to their healthy counterparts. However, it has also been shown that pulmonary microvascular permeability is decreased in severe HF patients, which would be expected to protect such patients from pulmonary edema (24).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it has been shown that a chronic increase in adrenergic drive, as occurs with HF, elicits a down-regulation of the β receptors central to lung fluid removal mechanisms (24). In combination, it is possible that the aforementioned changes in the pulmonary system associated with HF may conspire to increase fluid flux across the pulmonary vasculature while impairing fluid clearance from the alveoli and interstitial space, thus making HF patients more susceptible lung fluid accumulation relative to their healthy counterparts.…”
Section: Introductionmentioning
confidence: 99%